Negative biofeedback for enhancing proprioception training on wobble boards - Gopalai, Alpha; Senananayake, A. (Springer-Verlag Berlin Heidelberg, 2011)
Biofeedback has been identified to improve postural control and stability.A biofeedback system communicates with the humans’ Central Nervous Systemthrough many available modalities, such as vibrotactile. The vibrotactile nature offeedback is presented in a simple and realistic manner, making the presentationof signals safe and easy to decipher. This work presents a wobble board training routine for rehabilitation combined with real-time biofeedback. The biofeedback was stimulated using a fuzzy inference system. The fuzzy system had two inputs and one output.Measurements to test this rehabilitation approach was taken in Eyes Open and Eyes Close states, with and without biofeedback while subjects stood on the wobble board. An independent T-test was conducted on the readings obtained to test for statistical significance. The goal of this work was to determine the feasibilityof implementing a negative close-loop biofeedback system to assist in proprioceptortraining utilizing wobble boards.